2021
DOI: 10.1097/hjh.0000000000002801
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cortisol on blood pressure and hypertension-mediated organ damage in hypertensive patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
0
10
0
5
Order By: Relevance
“…There are also animal studies indicating a possible causal relationship between prenatal exposure to GCs and the occurrence of postnatally reduced number of nephrons and increased reactivity in the arterioles ( 45 , 47 , 48 ). The latter findings may contribute to the pathogenesis of hypertension ( 6 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are also animal studies indicating a possible causal relationship between prenatal exposure to GCs and the occurrence of postnatally reduced number of nephrons and increased reactivity in the arterioles ( 45 , 47 , 48 ). The latter findings may contribute to the pathogenesis of hypertension ( 6 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 94%
“…Cortisol serves a variety of important functions, including producing effects on the cardiovascular system and the kidneys that may give rise to systemic hypertension ( 6 ). Studies have shown negative effects due to early prenatal DEX treatment in the context of CAH in multiple biological functions ( 7-11 ).…”
mentioning
confidence: 99%
“…Окрім того, слід враховувати, що подібні тести проводяться в лабораторії за участю сторонніх людей (дослідників), що само по собі може викликати занепокоєність пацієнтів (ефект «білого халата»). У таких випадках видається значно простішим вивчати вплив стресорних подразників на рівень АТ та ЧСС у реальному житті людей (у тому числі й на роботі) за допомогою методу амбулаторного добового моніторування [15]. Саме за допомогою даного методу і було виділено варіанти стрес-індукованої АГ.…”
Section: рисунок 3 взаємодії індивідуальних та зовнішніх факторів які...unclassified
“…При амбулаторному моніторуванні або домашньому самомоніторуванні АТ показники в межах норми. Згідно з даними чотирьох популяційних досліджень, загальна поширеність АГ «білого халата» в середньому становить 13 % (діапазон 9-16 %), а серед хворих на АГ, які взяли участь у дослідженнях, -близько 32 % (діапазон 25-46 %) [15]. Фактори, пов'язані з підвищеною поширеністю АГ «білого халата»: вік, жіноча стать та статус некурця.…”
Section: варіанти стрес-індукованої артеріальної гіпертензіїunclassified
See 1 more Smart Citation